2009
DOI: 10.1097/yic.0b013e32832b6bf6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antipsychotic treatments on the motivation to eat: preliminary results in 153 schizophrenic patients

Abstract: Many aspects of the motivation to eat are involved in the impairment of adequate food intake and body weight control. The aim of this study was to evaluate, by adopting widely used eating questionnaires, the Three Factors Eating Behaviour Questionnaire (TFEQ) and the Dutch Eating Behavior Questionnaire (DEBQ), the associations of different antipsychotic medications with the food attitudes of 153 schizophrenic patients: we compared 93 individuals treated with atypical antipsychotics, 27 treated with conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 33 publications
7
57
4
2
Order By: Relevance
“…Interestingly, HAL has been shown to decrease the hedonic value of food (Galistu et al 2011;Hartfield et al 2003) but can also decrease satiety at a lower dosing range (Lee and Clifton 2012;Kaur and Kulkarni 2002). Notably, it has been proposed that obesity and addiction may share a reduction in striatal D 2/3 signaling (Tomasi and Volkow 2013), which may have implications for the observed increases in feeding disinhibition and binge eating observed in the aforementioned human studies (Blouin et al 2008;Kluge et al 2007;Sentissi et al 2009;Theisen et al 2003).…”
Section: Discussion/conclusionmentioning
confidence: 87%
See 2 more Smart Citations
“…Interestingly, HAL has been shown to decrease the hedonic value of food (Galistu et al 2011;Hartfield et al 2003) but can also decrease satiety at a lower dosing range (Lee and Clifton 2012;Kaur and Kulkarni 2002). Notably, it has been proposed that obesity and addiction may share a reduction in striatal D 2/3 signaling (Tomasi and Volkow 2013), which may have implications for the observed increases in feeding disinhibition and binge eating observed in the aforementioned human studies (Blouin et al 2008;Kluge et al 2007;Sentissi et al 2009;Theisen et al 2003).…”
Section: Discussion/conclusionmentioning
confidence: 87%
“…AAPs have also been associated with perturbations in the secretion and/or action of several hormones (insulin, leptin, ghrelin, adiponectin) and neuropeptides (NPY, AgRP, POMC) involved in the control of satiety and feeding behaviors (Jin et al 2008;Sentissi et al 2009;Song et al 2013). Results are, however, inconsistent; for example, Davoodi et al (2009) demonstrated increased meal size with acute OLA administration in rats was not associated with changes in NPY or POMC mRNA levels.…”
Section: Discussion/conclusionmentioning
confidence: 88%
See 1 more Smart Citation
“…33 The patients treated with atypical APDs were also more reactive to external eating cues. 34 Furthermore, a recent study reported that, consistent with the significant increase of body weight, food consumption and disinhibited eating, one week treatment with olanzapine enhanced both the anticipatory and consummatory reward response to food rewards in the brain reward circuitry, including the inferior frontal cortex, striatum and anterior cingulate cortex, but decreased activation in the brain region (the lateral orbital frontal cortex) thought to inhibit feeding behaviour.…”
Section: The Effects Of Anti-psychotic Medication On Appetite/food Inmentioning
confidence: 97%
“…[32][33][34] On the other hand, there is less understanding of to what extent changes of resting metabolism rate and activity/sedation affect weight gain associated with APD medication, although current evidence suggests that they may play an important role in the development of APD-induced weight gain. 19,35,36 Altered eating behaviours have been reported in a number of clinical studies with treatment involving various APDs.…”
Section: The Effects Of Anti-psychotic Medication On Appetite/food Inmentioning
confidence: 99%